The Impact and Correlation of Anxiety and Depression on Pressure Pain Threshold of Acupoints in Patients with Chronic Pelvic Inflammatory Disease - Chenxi Liao; Yu Tan; Kai Wang; Xin Wen; Xiang Hu; Yefang Huang; Ying Li (Pain Research and Management)
Background. Chronic pelvic inflammatory disease (CPID) is a clinically common gynecological disease. Patients experience chronic pelvic pain and often accompany with emotional dysfunction. However, the impact and correlation of anxiety and depression on pain sensitization is not completely known. Objective. To explore the differences and correlations among anxiety, depression, and pressure pain threshold (PPT) of acupoints in patients with CPID. Methods. One hundred and forty-seven patients with CPID were recruited. The Visual Analog Scale (VAS) and short-form McGill Pain Questionnaire (SF-MPQ) were used to assess pain. Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) were used to evaluate the emotional state of patients. The PPT of acupoints was collected using an electronic Von Frey by two licensed acupuncturists. Results. The CPID patients were divided into anxiety-depression group (group A) or nonanxiety-depression group (group B), according to the SAS and SDS scores. Finally, there were 73 patients in group A and 74 patients in group B. Group A had significantly higher SAS, SDS, VAS, and SF-MPQ scores than group B (P<0.05). In addition, significant differences were observed in the PPTs of ST28 (R), ST29 (R), SP10 (R), SP9 (R), SP9 (L), ST36 (R), and LR3 (L) between the two groups (P<0.05). No considerable differences in PPTs at the other acupoints were observed between the two groups. SAS scores showed a positive correlation with PPTs of ST29 (R), SP10 (R), SP9 (L), ST36 (R), and LR3 (L). No remarkable correlation was observed between the SDS scores and PPTs. Conclusion. Anxiety and depression can affect the PPT of some acupoints in CPID patients, which may provide a reference for acupoint selection for acupuncture treatment of CPID with emotional disorders. This trial is registered with ChiCTR2100052632.